Influence of varying dietary cation anions difference based diet on blood biochemical and immunological parameters in crossbred calves in summer months - Sambyal, Madhu suman (Indian Journal of Animal Nutrition, 2018)
An experiment was conducted in eighteen female crossbred Karan-fries calves to evaluate the effect of positive dietary cation anion difference (DCAD) based diet on dry matter intake (DMI), blood biochemical parameter and immunity status in a summer months. The calves were blocked into three equal groups on the basis of average body weight. The calves in control group receive basal diet and S1 and S2 group were offered with +250 /+350 mEq/Kg DM DCAD diet. The temperature humidity index (THI) was calculated at 07:30 am and 02:30 pm daily. It has been observed that there was no significant effect of varying DCAD diet on physiological variables (RR, PR and RT), though variations were observed due to changes in environmental temperature and THI. The overall DMI was significantly more (P<0.05) in S2 group(4. 93 kg/d) as compared to control (4.36 kg/d). Plasma glucose level were found to be similar in all the three groups There was no significant effect of varying DCAD diet on FRAP value, SOD and catalase activity. The plasma total Ig (mg/ml), IgG (ng/ml) and IgM (ng/ml) level was significantly more (P<0.05) in S2 group as compared to control, also similar trends observed for plasma T3 and T4 level.Plasma cortisol concentration was 4.24, 3.85 and 3.79 ng/ ml, in control, S1 and S2 groups, respectively showing significantly (P<0.05) low values in treatment groups as compared to control.It is inferred from the study that positive DCAD diet of +250 and +350 mEq/Kg DM improved the nutrient intake and immunity status by ameliorating heat stress.